The role of human capital in the system of education of Kazakhstan - Kairatbek Shadiyev, Aigul AuelbekovaNurlan Abdilda, Кasiya Кirdasinova, Asel Uskelenova, Dinara Mukhiyayeva (Opción, 2019)
This paper provides an overview of the economical evaluation of the current state of the higher education in Kazakhstan and the role of human capital in implementing the tasks of national economy. The authors of the article used the method of statistical analysis to determine the current trends in the development of the system of higher education. As a result, the present work systemizes the theorist-practical aspects of research of human capital in the education system based on the held researches. Moreover, relevant conclusions are made based on the findings, including taking into account the internal costs of research and development.